Diversity and Dynamics of Sand Flies (Diptera: Psychodidae) of Two Cutaneous Leishmaniasis Foci in the Fes-Boulemane Region of Northern Morocco - Talbi, Fatima Zahra; Faraj, Chafika; EL-Akhal, Fouad; El Khayyat, Fatiha; Chenfour, Driss; Janati Idrissi, Abdellatif; El Ouali Lalami, Abdelhakim (International Journal of Zoology, 2015)
Cutaneous leishmaniasis (CL) is an infectious disease caused by various species of Leishmania and transmitted by several species of sand flies (Diptera: Psychodidae). In order to evaluate the risk of leishmaniasis transmission in Fes-Boulemane, an investigation was carried out in two localities, Aichoun and Bouasseme, during 2011. From January to December, 1120 specimens were collected in Aichoun comprising six species belonging to two genera: Phlebotomus sergenti (76.07%), Phlebotomus longicuspis (9.01%), Phlebotomus perniciosus (8.48%), Phlebotomus papatasi (4.82%), Sergentomyia minuta, and Sergentomyia fallax. For Bouasseme, seven species were identified with Phlebotomus sergenti (60.39%) dominating, followed by Phlebotomus perniciosus (20%) and Phlebotomus longicuspis (12.15%). The remaining species, Phlebotomus papatasi, Phlebotomus ariasi, Sergentomyia minuta, and Sergentomyia fallax, were less prevalent. The activity of sand flies in both localities is marked by the dominance of Ph. sergenti with two peaks occurring in June and September. In order to obtain a better understanding of sand fly diversity among their species, results were analyzed by the ecological indices determinant: specific richness, the relative abundance, and Shannon-Weiner index (H′). Further studies of sand fly diversity should employ statistical tests and molecular analyses. This study can be useful in the implementation of appropriate future control measures.